Evaluation of the Level of Green building Criteria Implementation in the BSI Aceh Landmark Building Using the Greenship Method - Alfajri, Muhammad Safrul; Fuady, Mirza; Irzaidi, Irzaidi (Jurnal RAUT, 2025)
This study evaluates the implementation level of green building criteria in the BSI Aceh Landmark Building using the Greenship rating system for new buildings version 1.2, developed by the Green building Council Indonesia (GBCI). Amidst increasing concerns over climate change and environmental degradation, green buildings have emerged as a critical solution to reduce energy consumption and carbon emissions, especially in Indonesias construction sector. The research employs a qualitative descriptive approach, collecting data through field observations, document analysis, and interviews with building management and technical staff. The evaluation process involves a comprehensive checklist based on Greenship indicators, encompassing six categories and 46 criteria, with scoring to determine the buildings green rating from Bronze to Platinum. Findings reveal that the BSI Aceh Landmark Building meets all seven eligibility requirements, including land use, environmental management, disaster resilience, and accessibility for people with disabilities. The building demonstrates strong performance in site development, energy efficiency, and environmental management, though some challenges remain in documentation and the adoption of advanced technologies. This study provides practical recommendations for optimizing green building implementation in Aceh and contributes to the broader understanding of sustainable architecture in non-metropolitan areas, supporting the development of locally relevant green standards.